2022
DOI: 10.1186/s12866-022-02660-5
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the performance of phenotypic tests versus genotypic tests for the detection of carbapenemase-producing Gram-negative bacilli in resource-limited settings

Abstract: Background: Carbapenemase-producing Gram-negative (CPGN) bacteria impose life-threatening infections with limited treatment options. Rigor and rapid detection of CPGN-associated infections is usually associated with proper treatment and better disease prognosis. Accordingly, this study aimed at evaluating the phenotypic methods versus genotypic methods used for the detection of such pathogens and determining their sensitivity/specificity values. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Considering PCR as the gold standard test, the MHT was more sensitive than the CDT ( Table 5 ). This agreed with a study that reported MHT and CDT sensitivity as 65.62% and 55.22%, respectively ( 48 ). The IMP-EDTA CDT had higher specificity (66.7%) and accuracy (65%) compared with the MHT ( Table 5 ).…”
Section: Discussionsupporting
confidence: 93%
“…Considering PCR as the gold standard test, the MHT was more sensitive than the CDT ( Table 5 ). This agreed with a study that reported MHT and CDT sensitivity as 65.62% and 55.22%, respectively ( 48 ). The IMP-EDTA CDT had higher specificity (66.7%) and accuracy (65%) compared with the MHT ( Table 5 ).…”
Section: Discussionsupporting
confidence: 93%
“…The aim of performing phenotypic relatedness analysis was to provide a broad overview about the relevant abundance of antibiotic resistance among the collected isolates. A dendrogram showing the heatmap analysis of the P. aeruginosa isolates was constructed utilizing the Morpheus online software ( https://software.broadinstitute.org/morpheus/ (accessed on 18 December 2023) using Euclidean distances [ 23 ], to determine clonal relatedness.…”
Section: Methodsmentioning
confidence: 99%
“…This was created by Morpheus online software ( https://software.broadinstitute.org/morpheus/ accessed on 12 February 2023). using Euclidean distances as previously reported [ 26 ].…”
Section: Methodsmentioning
confidence: 99%